2023
DOI: 10.1007/s00127-023-02457-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 related adversity on the course of mental health during the pandemic and the role of protective factors: a longitudinal study among older adults in The Netherlands

Abstract: Purpose Many studies report about risk factors associated with adverse changes in mental health during the COVID-19 pandemic while few studies report about protective and buffering factors, especially in older adults. We present an observational study to assess protective and buffering factors against COVID-19 related adverse mental health changes in older adults. Methods 899 older adults (55 +) in the Netherlands were followed from 2018/19 to two pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Social and economic disruptions related to the COVID-19 pandemic posed a risk to marital satisfaction (Carrese-Chacra et al, 2023 ) and the well-being of families and communities (Prime et al, 2020 ). A recent study on Dutch older adults aged 55 years and over showed that regardless of pre-pandemic mental health, size of network was associated with symptoms of anxiety during the pandemic (Holwerda et al, 2023 ). A study during the COVID-19 pandemic focusing on the change in quality of relationships between married adults with children also showed a steeper decline in satisfaction with the relationship in women and in individuals with symptoms of depression (James et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Social and economic disruptions related to the COVID-19 pandemic posed a risk to marital satisfaction (Carrese-Chacra et al, 2023 ) and the well-being of families and communities (Prime et al, 2020 ). A recent study on Dutch older adults aged 55 years and over showed that regardless of pre-pandemic mental health, size of network was associated with symptoms of anxiety during the pandemic (Holwerda et al, 2023 ). A study during the COVID-19 pandemic focusing on the change in quality of relationships between married adults with children also showed a steeper decline in satisfaction with the relationship in women and in individuals with symptoms of depression (James et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study in Morocco highlighted the use of religiosity, and charity during COVID-19 [ 57 ]. In addition, based on findings from the Netherlands, a study stated that stimulating existing religious and spiritual resources may enable persons to function better in case of pandemics and other collective stressors [ 58 ]. The current study reported higher preventive coping such as avoiding going outside without purpose, preferring to stay home when not well, staying at least 6 ft. away from people, and covering mouth with tissue/inside of elbow while sneezing or sneezing coughing.…”
Section: Discussionmentioning
confidence: 99%